2006
DOI: 10.1179/016164106x152052
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunction of nitric oxide synthases as a cause and therapeutic target in delayed cerebral vasospasm after SAH

Abstract: Nitric oxide (NO), also known as endothelium-derived relaxing factor, is produced by endothelial nitric oxide synthase (eNOS) in the intima and by neuronal nitric oxide synthase (nNOS) in the adventitia of cerebral vessels. It dilates the arteries in response to shear stress, metabolic demands, pterygopalatine ganglion stimulation and chemoregulation. Subarachnoid hemorrhage (SAH) interrupts this regulation of cerebral blood flow. Hemoglobin, gradually released from erythrocytes in the subarachnoid space, dest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
52
1
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 97 publications
0
52
1
2
Order By: Relevance
“…The endogenous NOS inhibitor ADMA in cerebrospinal fluids was increased by the presence of bilirubinoxidized fragments, and disappearance of ADMA-hydrolyzing enzyme immunoreactivity in cerebral arteries in spasm decreased ADMA elimination; cerebrospinal fluid ADMA levels were associated with the degree and times of vasospasm (Pluta, 2005(Pluta, , 2006. Therefore, stimulation of ADMA-hydrolyzing enzymes and/or exogenous delivery of NO were suggested as therapeutic modalities to prevent and treat SAH.…”
Section: Therapeutic Measures In Animalsmentioning
confidence: 99%
“…The endogenous NOS inhibitor ADMA in cerebrospinal fluids was increased by the presence of bilirubinoxidized fragments, and disappearance of ADMA-hydrolyzing enzyme immunoreactivity in cerebral arteries in spasm decreased ADMA elimination; cerebrospinal fluid ADMA levels were associated with the degree and times of vasospasm (Pluta, 2005(Pluta, , 2006. Therefore, stimulation of ADMA-hydrolyzing enzymes and/or exogenous delivery of NO were suggested as therapeutic modalities to prevent and treat SAH.…”
Section: Therapeutic Measures In Animalsmentioning
confidence: 99%
“…19,27 Decreased functionality of this pathway following SAH has been linked to the pathophysiology of DCI including CVS. 58,69,71,77,85 Studies investigating the eNOS-NO-cGMP pathway have shown that inhibition of PDE-V has substantial beneficial effects. In animal SAH studies, PDE-V inhibition (mainly via administration of sildenafil, an FDA-approved selective PDE-V inhibitor) acutely reverses SAH-induced CVS, 2,28,31,32,34,42 reduces neuronal cell death, 32 restores impaired autoregulatory mechanisms, 73 and improves neurological outcomes.…”
mentioning
confidence: 99%
“…This effect is largely mediated by a downregulation of vasodilatory substances through depletion of NO and upregulation of vasoconstrictive substances, such as endothelin-1 and bilirubin oxidation products. [36][37][38] There is loss of NOS in vessels with cerebral vasospasm and severe endothelial dysfunction. 39 Strategies to augment NO and inhibit endothelin-1 have become therapeutic targets for improving outcome after SAH.…”
Section: Sah: Vasospasm and DCImentioning
confidence: 99%
“…34,35 Thick layering of blood around larger arteries is an important predictor of vasoconstriction, which results from a shift in the balance between the cerebral vasodilatory and the vasoconstrictive systems, as well as inflammation. 36 Periarterial oxyhemoglobin causes the release of vasoactive substances that result in vasoconstriction. This effect is largely mediated by a downregulation of vasodilatory substances through depletion of NO and upregulation of vasoconstrictive substances, such as endothelin-1 and bilirubin oxidation products.…”
Section: Sah: Vasospasm and DCImentioning
confidence: 99%